Green synthesis of silver nanoparticles using calabash (Crescentia cujete) fruit extract and their antimicrobial properties - Legaspi, Dyle S.; Fundador, Noreen Grace V. (2020)
Conventional methods in synthesizing silver nanoparticles (AgNPs) make use of toxic chemicals and are expensive; thus, green chemistry has become the current trend in metal nanoparticle synthesis. In this study, ethanolic calabash (Crescentia cujete) fruit extract was used for the synthesis of AgNPs. The total phenolic content and free radical scavenging activity of the extract were 0.017 mg gallic acid equivalent/mg extract and 1.963 mg/mL, respectively. The presence of surface plasmon resonance peak within the range of 416?426 nm confirmed the formation of AgNPs. An optimization study was conducted to determine the conditions that would lead to the formation of smaller-sized nanoparticles. The optimum conditions were 60 °C for 24 h. Based on the transmission electron microscopy analysis, the AgNPs were spherical in shape with a size ranging from 4?7 nm. The antimicrobial activity of AgNPs was determined using the resazurin microtiter assay. The minimum inhibitory concentration (MIC) of the AgNPs against Staphylococcus aureus and Escherichia coli was 6.25 μg/mL. It is also noted that AgNPs had a greater inhibitory effect than chloramphenicol. The findings of this study provide a facile and eco-friendly approach for the large-scale production of AgNPs using calabash fruit extract. This also suggests the potential of AgNPs for the treatment of antibiotic-resistant bacteria. (Author's abstract)